A study on superior-environment friendly red potato production development. Issue 1 (March 2021) - Rukmana, D; Rahmadanih; Tenriawaru, A N; Darwis; Arsyad, M; Rauf, R A
Abstract: Hasanuddin University team has succeeded in applying the seed production technology of the Kentang Raja - known as the Red Potato - through tissue culture technology seed production can be driven 5-fold over conventional systems; the seeds of the Red Potato G0 have been tested. The long-term outcomes of the research are: (1) strengthening the role of farmers in a sustainable manner in the environmentally friendly Red Potato agribusiness in South Sulawesi; and (2) establishing a business network as a partner of Red Potato farmers, and a participatory farmer-based synergy to develop sustainable Red Potato agribusiness in South Sulawesi. The research findings were: (1) net income of Red Potato farm of IDR. 43, 701, 700 per hectare per season at cost efficiency (R / C-ratio) of 1.92; large production costs are the costs of seed and labor; labor costs represent 1/3 of the value of revenue after deducting the cost of production facilities; (2) the general distribution pattern of Red Potato production is the pattern in which the Red Potatoes from the farmers are sold to Large Traders, then sold to Retailers and Consumers in traditional markets of Makassar, this pattern runs relatively constant, business networks. The research suggests (1) Red Potato commodities as new varieties produced by Hasanuddin University, the farmers need to get subsidized seed prices from the government in order to increase farmer's income and more vigorously develop Red Potato commodities; (2). The Gowa Regency Government needs to continuously improve the services to farmers and farmer groups through increasing the activities of the Agricultural/Rural Training Center and and the Agribusiness Sub-Terminal.